A novel long-wavelength fluorescent probe for discrimination of different palladium species based on Pd-catalyzed reactions. Issue 40 (10th May 2017) - Yu, Ting; Yin, Guoxing; Yin, Peng; Zeng, Ying; Li, Haitao; Zhang, Youyu; Yao, Shouzhuo
Abstract : We have synthesized a novel long-wavelength fluorescent probeMFC for detection of palladium (Pd 0 ). Abstract : We have synthesized a novel long-wavelength fluorescent probeMFC for detection of palladium (Pd 0 ). This probe not only shows high selectivity for palladium, but also could quickly discriminate different palladium species (Pd 0, Pd 2+, Pd 4+ ) in phosphate buffered solution. After the reaction with Pd(PPh3 )4, the UV absorption of the probeMFC shifts from 334 nm to 594 nm within a few minutes. The probeMFC conjugated with alkyl carbamate, which destroys the principle of intramolecular charge transfer (ICT) and shows weak fluorescence. Based on the Pd 0 -catalyzed Tsuji–Trost deallylation reaction, the fluorogen was released and the fluorescence intensity at 612 nm was observed with 13-fold enhancement along with an obvious color change from yellow to purple with low detection limit.